HUBUNGAN POLA PEMBERIAN MAKANAN DAN PENGETAHUAN GIZI IBU DENGAN KEJADIAN STUNTING - Permana, Aliffia Sri; Sulandjari, Siti (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2024)
Stunting is a failure to achieve childrens growth potential which can lead to future disturbances spesifically experiencing difficulties in achieving optimal physical and cognitive development. This study aims to analyze the correlation between nutritional knowledge and feeding patterns of mothers with the incidence of stunting toddlers aged 25-59 months. The type of research is a quantitative study with a cross sectional approach. The population of this study were mothers with toddlers aged 25-59 months as many as 270 people and a sample of 80 people were taken with the sampling technique using simple random sampling. Feeding patterns by mothers were measured using the Child Feeding Questionaire (CFQ) and nutritional knowledge was measured using tests. Data analysis used chi-square test. The results of the research show that there was a relationship between feeding patterns with incidence of stunting in toddlers (p=0.000) and there is no relationship between maternal nutritional knowledge with incidence of stunting in toddlers (p=0.281). Health workers are expected to provide education to mothers of toddlers regarding toddler nutrition, as well as evaluate the counseling that has been provided as an effort to prevent and overcome stunting.Stunting adalah kondisi di mana seseorang tidak dapat tumbuh dan berkembang sesuai dengan potensi genetiknya, yang berpotensi menimbulkan masalah di kemudian hari, termasuk hambatan dalam mencapai kemajuan fisik dan mental. Penelitian ini memiliki tujuan guna mencari tahu kaitan diantara wawasan gizi serta pola pemberian makanan ibu dengan kejadian balita stunting umur 25-59 bulan. Jenis penelitian ini ialah penelitian kuantitatif korelasional menggunakan pendekatan cross sectional. Populasi penelitian ini ialah ibu yang mempunyai balita umur 25-59 bulan berjumlah 270 orang, sebanyak 80 orang sampel penelitian yang diambil dengan metode simple random sampling. Pola pemberian makanan oleh ibu diukur menggunakan Child Feeding Questionaire (CFQ) dan pengetahuan gizi diukur menggunakan tes. Analisis hubungan antara variabel memanfaatkan uji Chi-square. Hasil penelitian mememperlihatkan adanya kaitan diantara pola makan bersama peristiwa balita stunting (p=0,000) serta tidak ada kaitan diantara pengetahuan gizi ibu bersama peristiwa balita stunting (p=0,281). Kader atau tenaga kesehatan diinginkan mampu memberi pengarahan bagi ibu balita tentang gizi balita, dan juga menjalankan evaluasi dari pengarahan yang sudah diberikan menjadi usaha mencegah menanggulangi stunting.